ANALISIS DAN PERANCANGAN PENGOLAHAN DATA ARSIP PADA KANTOR NOTARIS DAN PEJABAT PEMBUAT AKTA TANAH (PPAT) ISMET TAUFIK, S.H KOTA JAMBI - Dessy Setiawati; Noneng Marthiawati; Oka Ediansa (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2024)
Many companies, including the Notary Office and PPAT Ismet Taufik, S.H. in Jambi City, still rely on manual systems, leading to poorly organized archive data and inefficient data searches that hinder work processes. This research aims to analyze and design a web-based archival data processing system to improve data organization and search efficiency. Using the UML (Unified Modeling Language) methodology, this study incorporates use case diagrams, activity diagrams, and class diagrams. The system design follows a Prototype model visualized using the Canva application. The result is a design for a more effective and efficient archival data processing system tailored for the Notary Office and PPAT Ismet Taufik, S.H.